2014
DOI: 10.2337/db13-0417
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for Thioredoxin-Interacting Protein in Diabetes-Related Impairment of Angiogenesis

Abstract: Impaired angiogenesis in ischemic tissue is a hallmark of diabetes. Thioredoxin-interacting protein (TXNIP) is an exquisitely glucose-sensitive gene that is overexpressed in diabetes. As TXNIP modulates the activity of the key angiogenic cytokine vascular endothelial growth factor (VEGF), we hypothesized that hyperglycemia-induced dysregulation of TXNIP may play a role in the pathogenesis of impaired angiogenesis in diabetes. In the current study, we report that high glucose–mediated overexpression of TXNIP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 36 publications
5
46
0
1
Order By: Relevance
“…3 In the vasculature, a knockdown of Txnip was able to restore blood flow and rescue diabetes-related impairment of ischemia-mediated angiogenesis in diabetic mice with surgical introduction of hind limb ischemia. 36 Together, these findings support the important roles of Txnip in multiple organ damage induced by ischemia/reperfusion.…”
Section: Thioredoxin-interacting Protein Exacerbates Ischemia/reperfusupporting
confidence: 59%
“…3 In the vasculature, a knockdown of Txnip was able to restore blood flow and rescue diabetes-related impairment of ischemia-mediated angiogenesis in diabetic mice with surgical introduction of hind limb ischemia. 36 Together, these findings support the important roles of Txnip in multiple organ damage induced by ischemia/reperfusion.…”
Section: Thioredoxin-interacting Protein Exacerbates Ischemia/reperfusupporting
confidence: 59%
“…Although both molecular 28 and topological 5 observations indicate that the role of TxnIP in promoting oxidative injury extends beyond its negative regulation of Trx, augmented expression of the protein has been repeatedly associated with the development of diabetes complications. 5,[29][30][31][32] In this study, we found that depletion of EZH2, with either DZNep or shRNA, rendered cultured podocytes vulnerable to the deleterious effects of high-glucose concentrations, leading to an increase in ROS levels and cell death. The augmentation of high glucose-induced oxidative damage in podocytes was, at least in part, mediated by derepression of TxnIP shown by (1) increased podocyte TxnIP mRNA and protein abundance when EZH2-depleted cells were exposed to high-glucose concentrations and (2) abrogation of ROS accumulation by either TxnIP knockdown or Trx overexpression.…”
Section: Discussionmentioning
confidence: 87%
“…Previous reports provide compelling evidence that type 2 diabetes impairs arteriogenesis and angiogenesis (410). Several observations from the current study, however, suggest this may not be the sole mechanism.…”
Section: Discussionmentioning
confidence: 99%